2021
DOI: 10.1039/d1ob00983d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of off-target cleavage by RNase H using an artificial cationic oligosaccharide

Abstract: Sequence-dependent off-target effects are a serious problem of antisense oligonucleotide-based drugs. Some of these side effects are induced by ribonuclease H (RNase H)-mediated cleavage of non-target RNAs with similar base...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This data demonstrates that optimization of ASO size and the number of LNA nt provides a tool for finding balanced ASO sequence with moderate affinity and moderate specificity but does not resolve the affinity/specificity dilemma 19 . ASO modified by other artificial nucleotides 55 or conjugated with ASO/RNA complex stabilizing groups 56 , 57 should experience the same fundamental challenge.…”
Section: Antisense Oligonucleotides (Aso Agents)mentioning
confidence: 99%
“…This data demonstrates that optimization of ASO size and the number of LNA nt provides a tool for finding balanced ASO sequence with moderate affinity and moderate specificity but does not resolve the affinity/specificity dilemma 19 . ASO modified by other artificial nucleotides 55 or conjugated with ASO/RNA complex stabilizing groups 56 , 57 should experience the same fundamental challenge.…”
Section: Antisense Oligonucleotides (Aso Agents)mentioning
confidence: 99%
“…17 Most recently, we have reported that ODAGal4 is effective for modulating the mismatch discrimination by the RNase H cleavage. 19 Moreover, ODAGal is useful for the selective delivery of a siRNA to the liver cell by conjugating vitamin E to ODAGal. 20 Notably, it has been suggested that the presence of ODAGals does not disturb the gene silencing effect of siRNAs.…”
Section: Introductionmentioning
confidence: 99%